Impact of Salesmen Personality on Customer Perception and Sales (Global Journal of Management and Business Research, 2015)
The objective of our study is to know the impact of the salesmen personality on customer perception and sales. The study considers various personality traits that influence the customer thinking's regarding product and increase its sales. The study was based on primary data which was collected from 172 respondents by means of a questionnaire. Random Sampling Technique was applied and Statistical tool like SPSS software was used to first check the reliability of questionnaire and then correlation analysis in order to reveal the results of the research. The results indicate that the personality traits of salespeople influence both customer perception and sales. As the customer attraction is main focus of every business, the findings and recommendation of this research will help the managers to develop a deeper insight of research factors into salesmen personality development and restructure their strategies to capture maximum potential customers.
Keywords: salesperson personality; personality traits; customer2019; s relation; customer perception and sales